Long-range transport of air pollutants increases the concentration of hazardous components of PM2.5 in northern South America - M. P. Velásquez-García; M. P. Velásquez-García; M. P. Velásquez-García; K. S. Hernández; J. A. Vergara-Correa; R. J. Pope; R. J. Pope; M. Gómez-Marín; A. M. Rendón (Atmospheric Chemistry and Physics, 2024)
Long-range transport (LRT) of air pollutants from a range of sources can substantially enhance background pollution levels, especially in urbanized regions, which can exacerbate high-pollution episodes. In the Aburrá Valley (AV), Colombia, and other cities in northern South America, biomass burning (BB), dust, and volcanic degassing have been identified as sources of long-range aerosol transport. However, the impact of these sources on air quality and the characterization of these sources have yet to be thoroughly studied. This work investigates the influence of these sources on the chemical composition of PM2.5 during annual and intra-annual high-load aerosol events in the AV. We identified, tracked, and meteorologically characterized LRT events and evaluated their influence on PM2.5 concentration and chemical composition. We found that the LRT of aerosols from BB, dust, and volcanic degassing influenced approximately 13 %, 8 %, and 13 % of days in the year, respectively. We applied the positive-matrix-factorization (PMF) statistical model to quantify PM2.5 concentrations and chemical compositions for the different LRT event types (e.g., BB). For BB events, we identified large contributions from organic carbon (OC1 and OC2), F−, and secondary aerosol tracers (SO42-<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="34pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="98c07412ca463a3289ef0d23c4258b12"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-24-11497-2024-ie00001.svg" width="34pt" height="16pt" src="acp-24-11497-2024-ie00001.png"/></svg:svg> and NO3-<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="30pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="e60cf2b8b1907d178ba5f85379a9361c"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-24-11497-2024-ie00002.svg" width="30pt" height="15pt" src="acp-24-11497-2024-ie00002.png"/></svg:svg>). For dust LRT events, crustal mineral components, along with Ti and Ca, were the primary contributors to aerosol composition, while SO42-<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="34pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="c20686ed8f3fd8945175e0be8fa4b2a3"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-24-11497-2024-ie00003.svg" width="34pt" height="16pt" src="acp-24-11497-2024-ie00003.png"/></svg:svg>, Na, Al, and Ca were the primary contributors during volcanic events. The concentrations of some ions and toxic heavy metals (Cr, Mn, Cd, and Ni) were also elevated during BB and volcanic-degassing events. BB contributed the most to PM2.5 levels during the LRT events (∼11 µg m−3), while contributions from aerosols arising from dust and volcanic events were also substantial (<7 µg m−3). Our study identifies the Orinoco and the Middle Magdalena Valley as sizable sources of BB aerosols and Nevado del Ruiz as a source of volcanic aerosols. Additionally, we found that African dust reached the Andean region via the Caribbean route. As a result, we identify the need for future chemical-transport modeling studies in the region and new support strategies to manage internal and external pollution sources that degrade air quality in the AV and the surrounding region.